2005
DOI: 10.1562/2005-08-11-rn-646
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Anisotropy Imaging Reveals Localization of meso‐Tetrahydroxyphenyl Chlorin in the Nuclear Envelope

Abstract: We have measured the intrinsic fluorescence anisotropies of six photosensitizers in homogeneous solution, and we have imaged the anisotropies of these sensitizers in tumor cell monolayers using polarization-sensitive laser-scanning confocal microscopy. The intrinsic anisotropies are unremarkable and are within the approximate range of 0.2-0.27. In cells, however, very interesting behavior is exhibited by meso-tetrahydroxyphenyl chlorin (mTHPC). Polarization-sensitive images of mTHPC's fluorescence show a prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…We hypothesize that there may be two corresponding distinct 1 O 2 lifetimes and that it might be possible to monitor these by SOL and so determine the relative contributions of photodamage of the different organelles to the therapeutic outcome. Similarly, Foster et al recently demonstrated that the photosensitizer meso‐tetrahydroxyphenyl‐chlorin (mTHPC) can be found in the nuclear envelope as well as in cytoplasmic organelles (60). Using time‐resolved SOL measurements, it may be possible to differentiate these two components and to assess the fraction that each contributes to the PDT dose.…”
Section: Fundamental Issues and Future Directionsmentioning
confidence: 95%
“…We hypothesize that there may be two corresponding distinct 1 O 2 lifetimes and that it might be possible to monitor these by SOL and so determine the relative contributions of photodamage of the different organelles to the therapeutic outcome. Similarly, Foster et al recently demonstrated that the photosensitizer meso‐tetrahydroxyphenyl‐chlorin (mTHPC) can be found in the nuclear envelope as well as in cytoplasmic organelles (60). Using time‐resolved SOL measurements, it may be possible to differentiate these two components and to assess the fraction that each contributes to the PDT dose.…”
Section: Fundamental Issues and Future Directionsmentioning
confidence: 95%
“…Then 1 O 2 ; either directly or associated to the formation of secondary reactive oxygen species (superoxide anion radical and hydrogen peroxide), causes damage to different cellular structures. Unlike radiotherapy, which targets mainly tumor cell DNA, Type II phototoxic reactions take place in the nuclear envelope, mitochondria, or plasma membrane [254,255]. Psoralens are plant derived tricyclic furocoumarins that have been used as primary phototoxic molecules since more than three decades in PUVA (psoralen+ ultraviolet A) therapy [256].…”
Section: Polyphenol-based Photodynamic Therapy (Pdt)mentioning
confidence: 99%
“…and was optimized to allow functionalization with both protected and deprotected carbohydrates in high yields. A sequential "double-click" process was used to obtain a new class of bismodified 5,10-diglycoporphyrins (263) In continuation of this initial work, a significantly large library of mono-, di-and trideprotected glycoporphyrins (316)(317)(318)(319)(320)(321)(322)(323)(324)(325)(326)(327)(328)(329)(330)(331)261) were synthesized with monosaccharides and for the first time, synthetic disaccharides and trisaccharide [33] . These studies also provide the first examples of bismodified glycosylated porphyrins and a significant highlight was the ligation of the synthetic trisaccharide Lewis X , a histo-blood group antigen.…”
Section: Organometallic Coupling Reactionsmentioning
confidence: 99%
“…The localization of each individual PS is different. mTHPC has been identified to localize in the nuclear envelope [330] while δ-aminolevulinic acid (ALA) localizes in the mitochondria and methylene blue in lysosomes [331] . The mechanism of uptake of PSs has not been clarified.…”
Section: Basic Principle Of Pdtmentioning
confidence: 99%